Peranan Penyuluh Swadaya dalam Mendukung Intensifikasi Kakao di Kabupaten Sigi Provinsi Sulawesi Tengah - Riana Riana; Ninuk Purnaningsih; Arif Satria (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2015)
Self-support extension agents is the main actors who are successful in their business and other community members with his own conscience willing and able to become a counselor. The role of self support extension agents is needed to support the role of civil servants as an alternative that is deemed in accordance with UU No. 16 2006th. But there are still many people, including the main actors themselves who do not know the important role of the non-extension. The purpose of this study is to analyze the role of self-support extension agents in supporting intensification extension cocoa viewed from the aspect of agribusiness. This research is descriptive quantitative survey method with descriptive analysis approach and quantitative paradigm. Research carried out in the Sigi district of Central Sulawesi, which became one of the central largest cocoa producing. The sample in this study is a cocoa farmer extension built by self-help by using the method of proportional cluster random sampling as 96 people. Overall results of farmers' perceptions of the role of self-support extension agents was that extension workers has been instrumentalin supporting themselves-intensification cocoa butonly dominant in farming sector. This happened because the they just get extension related to the cultivation. Whereas if the extension self-given knowledge relating to the harvest and post-harvest and marketing, the role will become more important as supported also by extension the role of self-support extension agents in motivating and help the farmers in the problem solving.Keywords: role, self-support extension agents, cocoa, farmer’s perception